Students' Views of the Use of Video Conferencing to Teach Speaking in Indonesian Higher Education - Aeni, Nur; Natsir, Nasrah (Celebes Journal of Language Studies, 2022)
This study attempts to describe how students view the use of Google Meet during the English language learning process. State University of Makassar was the site of this study. Student participants in this study were those attending State University of Makassar. Interviews were used by the researcher as a data collection tool. Based on the study's findings, the researchers discovered that students have both good and negative attitudes on using Google Meet for video conferencing during the learning process. Students' good attitudes can be seen in their readiness to participate in video conferences, enthusiasm for a variety of movements, development of their skills in using the learning tools, and respect and appreciation for others' abilities and disabilities. While the negative attitude was the students don’t attend the class and not participate the group project as well, and also if they cannot speak as well during video conferencing, they wouldn’t participate the class, they decided to keep silent and do not follow the instruction from the lecturer.